APPLICATION OF FEM TO PROBLEMS OF OPTIMAL STRUCTURAL DESIGN OF RAILWAY TRANSPORT - Kostrytsia, S. A. (Science and Transport Progress, 2003)
The possibility of using the finite elements method for optimal designing of railway rolling stock has been considered. The general optimization scheme, based on the gradient projection method, has been proposed.